Implication of diabetes mellitus in telomere length and alteration in some age related cell senescence markers of aged men in Kurdistan region-Iraq - Khafar, Kaniaw Rafat; Kakey, Dr. Esmail S (Kurdistan Journal of Applied Research, 2022)
Indications of cell maturing including telomere length and mitochondrial work, just as oxidative pressure and incendiary markers affect one another and structure a complicated organization, which all influenced in age related sicknesses, for example, diabetes mellitus. For this cause, this current investigation was designed to study and compare of some oxidative and molecular markers in healthy aged and diabetic aged men older adults. The study design was the setting of a medium private laboratory with participants being common people, which was classified into three groups according to age and health complication, control young, healthy aged, and diabetic aged groups. Blood sera was obtained for oxidative status including catalase (CAT), superoxide dismutase (SOD), Total antioxidant capacity (T-AOC), 8-hydroxy-2’-deoxyguanosine (8-OHdG), and malondialdehyde (MDA)) and molecular markers (including telomere length (T/S) and mitochondrial DNA copy number (mtDNA)). The findings highlighted that oxidative and molecular markers have significant changes with ageing and high changes significantly associated with diabetes mellitus of aged group. In conclusion, various oxidative stress, cell and mitochondrial biomarkers have been affected by normal ageing and the effects of ageing were complicated significantly in diabetic aged elderly.